15 + 2x - 4 = 9x + 11 - 7x
2x + 11 = 2x + 11
always true
2x + 3(4x - 1) = 2(5x + 3) + 4x
2x + 12x - 3 = 10x + 6 + 4x
14x - 3 = 14x + 6
never true
Start with parentheses first
Afterwards do exponents
Next do either multiplication or division (L to R)
Then Addition and Subtraction (L to R)
__________________________________________
Then solve to find your answer
Answer:
4949/200=
Step-by-step explanation:
It's the first one, an algebraic expression contains variables
(x + 1)·(x + 1 + 11) = (x + 4)·(x + 4 + 1) --> x = 2
Tools like "photomath" are able to help you solving such equations.